Group Counseling with Psychodrama and Sociodrama Techniques to Improve Emotional Intelligence (Jurnal Bimbingan Konseling, 2019)
This study aimed to examine the model of group counseling with psychodrama and sociodrama techniques to improve Senior High School students’ emotional intelligence. Moreover, the method used in this study was quasi-experimental by using One Group Pre-test – Post-test design involving 15 students of the tenth grade of Public Vocational High School 1 Donorojo (SMK Negeri 1 Donorojo) chosen through purposive sampling technique. Further, the data normality test was done by using Kolmogorov-Smirnov, and the effectiveness of the model was done by using the Wilcoxon signed rank test. The results showed that the model of group counseling with psychodrama and sociodrama techniques was effective to improve students’ emotional intelligence (z = 3.409, p < 0.01). At last, the discussion of the findings of this study is aimed at asserting the effectiveness of the model of group counseling with psychodrama and sociodrama techniques to improve emotional intelligence.